How stable are Parkinson's disease subtypes in de novo patients: Analysis of the PPMI cohort?. (July 2016) - Simuni, Tanya; Caspell-Garcia, Chelsea; Coffey, Christopher; Lasch, Shirley; Tanner, Caroline; Marek, Ken; ,
Abstract: Objective: To determine the frequency and stability over time of the subgroup characterization of the tremor dominant (TD) versus postural instability gait disorder dominant (PIGD) Parkinson's disease (PD) in de novo patients. Background: There is a substantial body of literature on the clinical sub classification of PD into TD versus PIGD subtype. However, there are limited data on the stability of this classification especially in early disease. Methods: Parkinson's Progression Markers Initiative (PPMI) is a longitudinal case control study of de novo, untreated PD participants at enrollment. Participants undergo a number of assessments including the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS). TD versus PIGD subtype was defined based on the previously published formula. We report one-year analysis data. Results: 320 of 423 PD recruited subjects had data on subtype classification at year 1 and were included in the analysis. 228 (71%) were classified as TD, 56 (18%) as PIGD and 36 (11%) as indeterminate at baseline. At 12 months, 39% PIGD and 18% TD shifted subtypes: 29% PIGD shifted to TD and 11% to Indeterminate; 10% TD shifted to PIGD and 8% to Indeterminate. The classification was not affected by the dopaminergic treatment (p = 0.59). Conclusions: TD versus PIGD subtype classification has substantial variability over first year in PD de novo cohort specifically for PIGD subtype. Dopaminergic therapy does not impact the change of the PD subtype. This instability has to be taken into consideration specifically when establishing correlations with the biomarkers and for long term prognostication. Highlights: The TD/PIGD subtype classification in early Parkinson's disease (PD) has significant variability. The change in classification is highest in the PIGD subset. Dopaminergic therapy does not impact the change of the PD subtype.